Algebra for college students - Miller, Julie (McGraw-Hill, 2004)
Algebra for College Students is an insightful text written by instructors who have first-hand experience with students of developmental mathematics. The authors introduce functions in Chapter 4 and do a very thorough treatment, devoting the entire chapter to the concept of functions. With such a solid foundation to build from, students will experience greater success when they encounter other function-related topics in later chapters, such as polynomial functions; quadratic functions; radical functions; and others. The authors have crafted the exercise sets with the idea of infusing review. In each set of practice exercises, instructors will find a set of exercises that help students to review concepts previously learned, and in this way, students will retain more of what they have learned. The exercise sets also contain translating expressions exercises which provide students with an opportunity to convert from English phrases to mathematical symbols and from mathematical symbols to English phrases, thus helping students to strengthen their command of mathematical language. Moreover, the applications found in the exercise sets are based on real-world data, which helps to promote students' interest in mathematics, and in turn, may serve to motivate and engage them.